Non-Muslim reaction towards Islamic banking / Fuad Rahady Mohd Ayob - Mohd Ayob, Fuad Rahady (Faculty of Business and Management, 2014)
Islamic banking is an abstract concept until the first half of the twentieth century. In Malaysia, it has been almost three decades when the first Islamic bank makes its debut. Islamic banks have to compete with its rival, conventional banks which have longer history than Islamic banks. For this competition, Islamic banks have to know reaction of Malaysians towards it. Islamic banks not only available for Muslims, but it also available for non-Muslims as well. In Malaysia, 40% of the population is non- Muslims and hence non-Muslims market is equally important to Islamic banks. The purpose of this research is to examine the reaction of non-Muslims in Malaysia of Islamic Banking products and services. A total of 280 respondents from different cities in Malaysia are selected for the purpose of this study. For the analysis, Pearson Correlation Coefficient was adopted to analyse the results. The results show that more than half of the respondents are aware of the Islamic banking in Malaysia but they do not aware of most of the products and services offered by Islamic banks. Non-Muslims understanding level towards Islamic bank concepts are at average level but they do not understand most of the Arabic terms. The perceptions of non-Muslims towards Islamic banks are varied among themselves. This study also provides theoretical and managerial implications for the Islamic bankers to attract non-Muslims customers and recommendations for future research in Islamic Banking.